High Temperature Dynamic Tension Behavior of Titanium Tested with Two Different Methods. (2017) - Hueto, Francisco; Hokka, Mikko; Sancho, Rafael; Rämö, Jari; Östman, Kauko; Gálvez, Francisco; Kuokkala, Veli-Tapani
Abstract: In this work, the dynamic response of Ti6Al4V alloy at high temperature was studied using the Split Hopkinson Pressure Bar –SHPB- apparatus with two different heating systems. The first device uses direct electric current to heat the sample to the testing temperature in a fraction of a second, whereas the second device uses a furnace to heat the sample and as a consequence, short sections of the bars, in few minutes. Tension tests were carried out at strain rates up to 1500 s -1 and at temperatures ranging from room temperature up to 700 °C. The conventional strain gauge measurements from the pressure bars were used to obtain the stress–strain curves and the Johnson-Cook material model was used to fit the results of the tests. High speed photography and digital image correlation were used to quantify the total strain during the test. The plasticity of the titanium alloy clearly increases as the temperature is increased. The maximum strains, obtained from the stress-strain curves, also increase when the temperature is increased from room temperature. DIC results, however, show clear differences in the maximum strain before failure with respect to the values obtained from strain gauges measurements. The maximum strain in the gauge section of the sample prior to failure increases steadily as the testing temperature is increased. At 60 °C, the strains within the gauge section reach values almost 50% just before failure. At 300 °C, the maximum strains are close to 65%, and at 700 °C the maximum strains extend close to 80%.